Photofate of Tetrabromobisphenol-A in the Arctic: Role of photofluence and dissolved organic matter - Robyn C. O’Halloran; Jill Kerrigan; Lauren E. O’Connor; Jennifer J. Guerard; Kimberly J. Hageman; Yu-Ping Chin (Arctic, Antarctic, and Alpine Research)
Polybrominated diphenyl ethers (PBDEs) used in consumer goods and flame retardants have been replaced by alternatives such as tetrabromobisphenol A (TBBPA). TBBPA does not readily undergo global distal transport, but local sources still threaten aquatic ecosystems. We studied the photofate of TBBPA with a specific focus on how Arctic-derived dissolved organic matter (DOM) affects its reaction kinetics, degradation pathways and formation of photoproducts in artificial and natural sunlight. Our results corroborate earlier studies that reveal a pH-dependent trend in TBBPA’s direct photolysis with longer degradation times for its acidic form. DOM either plays no role or it slightly reduces TBBPA’s rate of photodegradation via inner-filter effects. Photolysis experiments conducted at our Arctic field site, Toolik Lake Field Station, revealed slower than anticipated degradation, which magnified the half-life significantly during in-lake experiments. Importantly, the composition of DOM was found to influence the type and distribution of TBBPA photoproducts formed, which suggests that different degradation pathways occur in the presence of DOM. These findings provide valuable insights into the intricate interplay of environmental variables that govern the fate of TBBPA in sunlit aquatic ecosystems globally.